Are environmental services and bio-economy antagonist? - Rojas-Briales, Eduardo (Natural Resources Institute Finland, Luke, 2016)
Environmental services were at the core of the birth of forest science as the linkage to water and watershed shows even in the name of the Faculties and profession, especially in the Alpine and Mediterranean countries. The wake-theory (Dietrich 1953) recognized the relevance of environmental services but understood them automatically covered by a sustained yield conventional forestry. During the late 70s and following 3 decades, environmental services from forests, especially biodiversity and climate change, gain attention and it was evident that the low cost option of the wake theory eroded due to the fact that society wished a higher level of environmental services and increasingly extended areas of forests lost any profitability based on wood use.